TEKNIK BUDIDAYA UDANG DENGAN SISTEM POLIKULTUR DI KELURAHAN TAMARUPA KEC. MANDALLE KABUPATEN PANGKEP - Saenong, Muhammad; Harlina, Harlina (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2022)
Pangkajene Islands Regency is a coastal area where most of the population depends on their life as aquaculture farmers. In this village there is a farmer group "Sipakaenre II" who will become partners in this community service activity. The main problem faced by the shrimp farming farmer group “Paraikatte”, Tamarupa Sub-district, Kec. Mandalle (Partner) in managing his business is the low production in milkfish cultivation because the cultivation activities are still conventional with the monoculture method and the high price of feed. Recently, the price of factory-made feed (pellets) has increased significantly. This service activity aims to increase the production and income of farming communities in the coastal area of ​​Tamarupa Village by conducting: 1) Counseling to groups of pond farmers to provide knowledge, understanding and skills in CBIB-based polyculture shrimp farming techniques, 2) Introduction of polyculture-based shrimp farming technology. CBIB so that farmers can increase production by obtaining yields from both commodities in one cycle of cultivation. 3) Counseling/assistance on the application of group cultivation techniques in the application of the CBIB-based polyculture shrimp farming system. The approach method offered to partners to achieve the objectives of this community partnership program is a participatory method in which partners are directly involved in the implementation of activities from preparation to implementation of these activities. The implementation of the approach method is in the form of counseling and training or demonstration. After this activity is carried out: 1) There is an increase in understanding, knowledge and skills of farmer group partners about shrimp culture technology with a CBIBt-based Polyculture system, 2) An increase in aquaculture production due to maintaining two commodities simultaneously in one cultivation business cycle.